Estimation of voltage waveform at top of transmission line tower struck by lightning of negative and positive polarity - Yevgeniy Trotsenko (Technology Audit and Production Reserves, 2021)
The object of research is a circuit that simulates a lightning strike to a tower of 220 kV power transmission line, taking into consideration the reflection of a current wave from 10 nearest towers. Computation of the voltage arising at the top of the struck tower is necessary further to determine the lightning performance of transmission line by various methods. The lightning current has several maxima, in the case of a positive impulse polarity and, accordingly, several minima, in the case of a negative polarity, which are generally being called peaks. In addition, the lightning current impulse has a non-constant steepness in the entire area of current rise up to the first peak. The approximation of the real lightning current by simplified mathematical expressions cannot take into account all its real features. For a more detailed study of transient processes caused by thunderstorm activity, there is a need to use oscillograms of real lightning currents when modeling.